"Please help us with important research": A retrospective analysis examining the impact of research invitation and participation on subsequent blood donor behavior. Issue 10 (9th September 2022) - Kruse, Sarah P.; Nguyen, Lilly; Karki, Surendra; Thorpe, Rachel; Davison, Tanya E.
Abstract: Background: As over‐communication can negatively impact consumer behavior, it is important to understand the impact of research communication on donors' future donation behavior. The aim of this study was to determine the effect of (i) being invited to participate in research, and (ii) participating in that research, on future donation behavior. Study Design and Methods: A retrospective cohort analysis was conducted with 36, 418 donors who were invited to participate in one of 17 research projects, and a matched control group of 36, 252 non‐invited donors. Poisson regression models were used to examine the associations between invitation or participation in the studies and the likelihood of creating an appointment to donate and attending an appointment at 1, 3, and 6 months. Results: Donors were significantly more likely to create an appointment within 14 days of receiving an invitation compared to controls (RR: 1.91, 95% CI 1.81–2.02), and to return to donate at 1 (RR:1.18, 95% CI 1.13–1.24), 3 (RR:1.10, 95% CI 1.07–1.13) and 6 (RR:1.11, 95% CI 1.09–1.13) months compared to non‐invited controls. Donors who participated in the research were more likely to return than control donors at all time points, while donors who were invited but did not participate were also likely to return more at 1 month (RR:1.06, 95% CI 1.00–1.11) and 6 months (RR:1.03, 95% CI 1.00–1.5) than non‐invited controls. Discussion: Our findings suggest that research participation is positively associated with future donor behavior and provides reassurance that contacting donors for research does not negatively impact blood collections.